A Cyclopalladated BODIPY Construct as a Fluorescent Probe for Carbon Monoxide. Issue 14 (27th April 2022) - Çevik Eren, Merve; Eren, Ahmet; Dartar, Suay; Buse Tütüncü, Büşra; Emrullahoğlu, Mustafa
Abstract: By introducing a palladium ion into the backbone of BODIPY, we devised a cyclopalladated BODIPY construct that was almost non‐emissive in the absence of any analyte but became highly fluorescent upon interacting with carbon monoxide (CO) in solution and in living cells. A process of ortho ‐carbonylation and depalladation mediated by the specific binding of CO to palladium, promoted the release of the heavy atom from the fluorophore and consequently generated a fluorescence signal with an exceptionally high (60‐fold) enhancement ratio. Abstract : A BODIPY‐based palladacycle displays a selective turn‐on type fluorescent response towards carbon monoxide (CO) both in solution and living systems. Following an ortho ‐carbonylation/depalladation reaction pathway mediated by the addition of CO, the non‐fluorescent dye rapidly transforms into a new structure and induces a fluorescence response clearly observable with the naked eye.